French revolutionaries in the Ottoman Empire: diplomacy, political culture, and the limiting of universal revolution, 1792-1798 - Firges, Pascal (Oxford University Press, 2017)
"The effects of the French Revolution reached far beyond the confines of France itself. The Ottoman Empire, ancient ally and major trading partner of France, was not immune from the repercussions of the 'Age of Revolutions', especially since it was home to permanent French communities with a certain legal autonomy. French Revolutionaries in the Ottoman Empire examines, for the first time, the political and cultural impact of the French Revolution on Franco-Ottoman relations, as well as on the French communities of the Ottoman Empire. The modern interpretation of revolutionary ideological expansionism is strongly influenced by the famous propaganda decree of 19 November 1792 which promised 'fraternity and help to all peoples who wish to recover their liberty', as well as the well-studied efforts to export the Revolution into the territories conquered by the revolutionary armies and to the various Sister Republics. Against all expectations, however, French revolutionaries in the Ottoman Empire exhibited neither a 'crusading mentality' nor a heightened readiness to use force in order to achieve ideological goals. Instead, as this volume shows, in matters of diplomacy as well as in the administration of French expatriate communities, revolutionary policies were applied in an extremely circumspect fashion. The focus on the effects of the French regime change outside of France offers valuable new insights into the revolutionary process itself, which will revise common assumptions about French revolutionary diplomacy. In addition, Pascal Firges takes a close look at the establishment of the new political culture of the French Revolution within the transcultural context of the French expatriate communities of the Ottoman Empire, which serves as a thought-provoking point of comparison for the emergence and development of French revolutionary political culture."--
Literaturverzeichnis: Seite 260-272
Hier auch später erschienene, unveränderte Nachdrucke
Dissertation erschienen unter dem Titel: On Silent Feet: French Revolutionary Politics and Culture in the Ottoman Empire, 1792-1798
Keywords: France -- Foreign relations -- Turkey -- 1789-1815; France -- History -- Revolution, 1789-1799 -- Influence; Turkey -- Foreign relations -- France -- 18th century; France -- Foreign relations -- Turkey; Turkey -- Foreign relations -- France; France -- Foreign relations -- 1789-1815; Turkey -- Foreign relations -- 18th century; Hochschulschrift; Geschichte 1792-1798; Osmanisches Reich; Französische Revolution; Außenpolitik; Frankreich